A New Species of Atemelia (Lepidoptera, Yponomeutoidea, Praydidae) Feeding on the Ornamental Shrub Mahonia (Ranunculales: Berberidaceae) in Chile. (1st March 2014) - Sohn, Jae-Cheon; Alba, Margarita Peralta
Abstract: A new species of Praydidae, Atemelia mahonivora, sp. nov., is described from Chile based on adults, larvae, and pupae. This is the first species of Atemelia from the Neotropical region. Genitalia characters support the synonymy of Atemelia and Orinympha and the distinctiveness of Atemelia from Prays . Keys to all known species of Atemelia are provided. Atemelia mahonivora is a potential pest species of the economically important plant genus Mahonia . Berberidaceae is recorded as a host plant family of Praydidae for the first time.